2013
DOI: 10.1155/2013/518780
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol and Copper Affect Learning and Memory in the Rabbit

Abstract: A rabbit model of Alzheimer's disease based on feeding a cholesterol diet for eight weeks shows sixteen hallmarks of the disease including beta amyloid accumulation and learning and memory changes. Although we have shown that feeding 2% cholesterol and adding copper to the drinking water can retard learning, other studies have shown that feeding dietary cholesterol before learning can improve acquisition and feeding cholesterol after learning can degrade long-term memory. We explore the development of this mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 152 publications
(152 reference statements)
3
12
0
2
Order By: Relevance
“…However, statistical analysis of EPSP 2 /EPSP 1 revealed no group differences. This supports the contention that dietary concentrations may not significantly influence presynaptic function in hippocampus and thus pre-synaptic function may not be the major contributor to the altered behavioral performance induced by dietary cholesterol concentrations (Schreurs et al, 2003; Schreurs et al, 2007b; Schreurs et al, 2012; Schreurs, 2013). …”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…However, statistical analysis of EPSP 2 /EPSP 1 revealed no group differences. This supports the contention that dietary concentrations may not significantly influence presynaptic function in hippocampus and thus pre-synaptic function may not be the major contributor to the altered behavioral performance induced by dietary cholesterol concentrations (Schreurs et al, 2003; Schreurs et al, 2007b; Schreurs et al, 2012; Schreurs, 2013). …”
Section: Resultssupporting
confidence: 78%
“…Cholesterol is vital to synaptic transmission and plasticity as cholesterol depletion by MβCD can reduce LTP at hippocampus Schaffer collateral synapses (Koudinov and Koudinova, 2001; Maggo and Ashton, 2014) or even block LTP expression induced by HFS (Frank et al, 2008; Maggo and Ashton, 2014). Our data revealed dietary cholesterol may increase LTP expression at a low concentration but lead to a pronounced LTP reduction at higher concentrations which may contribute to the cognitive impairments in cholesterol fed animals (Darwish et al, 2010; Schreurs et al, 2012; Schreurs, 2013; Schreurs et al, 2013). These findings are consistent with a previous report showing decreased N-methyl-D-aspartate related postsynaptic currents in hippocampal CA1 neurons from cholesterol fed rats (Dufour et al, 2006).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In this case, we used two-tone discrimination of the rabbit NMR followed by a 2% cholesterol diet with or without 0.12 ppm copper added to the drinking water to determine whether rabbits fed cholesterol could remember the original task followed by reversal of that discrimination to determine whether rabbits could acquire a difficult new task which has been shown to be dependent on the hippocampus (Berger & Orr, 1983; Churchill et al, 2001; Knuttinen, Power, Preston, & Disterhoft, 2001; Miller & Steinmetz, 1997). One prediction might be that cholesterol decreases the ability to remember the original discrimination but facilitates the acquisition of discrimination reversal and that the addition of copper might reverse those effects because it can retard learning (Schreurs, 2013; Sparks & Schreurs, 2003). …”
Section: Introductionmentioning
confidence: 99%
“…In accordance with this observation, the levels of miR-26b were reported to be significantly elevated in human postmortem brains, starting from early stages of AD (Braak III), and it has been suggested that contribute to the progression of the disease by regulating the hyperphosphorylation of tau through the regulation of this target retinoblastoma protein (Rb1) [141]. Recently, the group of Ghribi describes the upregulation of miR-26b [167] and the concomitant reduction of leptin levels [168] in the brain cortex of rabbits fed with a diet supplemented with 2 % cholesterol, which induce the development of full-blown AD pathology, including cortical Aβ deposits and tangles, and other pathological markers also seen in human AD brains [169][170][171][172][173][174]. Additionally, they describe the deregulation of other miRNAs previously reported to be altered in human AD samples, including miR-125b, miR-98, miR-107, and miR-30, along with three members of the let-7 family [167].…”
Section: Metabolic Manipulations and Mirna Deregulations In The Brainmentioning
confidence: 99%